Pengurangan Sampah Masuk ke Zona Aktif TPA Kedungdowo dari TPST Kartoharjo dan TPS3R Payaman - Nurkhalisha, Seren; Novembrianto, Rizka (Jurnal Serambi Engineering, 2025)
Waste problems in Nganjuk Regency are becoming more complex due to population and economic growth, resulting in an increase in the volume of waste entering the Kedungdowo TPA Active Zone. An integrated waste management system is needed. We must apply and maximize the role of TPST and TPS3R. The objective of this study was to ascertain the amount of residual waste entering the Kedungdowo TPA Active Zone after waste management at TPST Kartoharjo and TPS3R Payaman. Additionally, the study sought to determine if there is a reduction in residue entering the Kedungdowo TPA Active Zone when management is carried out and when it is not. We conducted this research through field observations and interviews with the person in charge of TPST Kartoharjo, TPS3R Payaman, and Kedungdowo landfill. This approach allowed us to obtain concrete information and data for each place. The results are clear: residual waste entering the Kedungdowo Landfill Active Zone in January and February from TPST Kartoharjo amounted to 90,329.4 kg, and 24,359.888 kg from TPS3R Payaman. The reduction of residual waste entering the Kedungdowo TPA Active Zone by TPST Kartoharjo and TPS3R Payaman is projected to reach 57,909.488 kg in January and 56,779.8 kg in February. The Kedungdowo TPA Active Zone will reduce the residue entering the facility by 1,541,378 kg and 1,346,924 kg after management, compared to 1,612,144 kg and 1,406,904 kg without management.